2007
DOI: 10.1002/gps.1829
|View full text |Cite
|
Sign up to set email alerts
|

Impact of personality on termination of short‐term group psychotherapy in depressed elderly outpatients

Abstract: Personality traits may be important clinical determinants of the quality of termination process in both group psychotherapy and therapeutic community settings for elderly depressed patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…That study, however, found no effects for depressiveness or warmth. Another small study, which did not measure depression severity, found that facets of openness and agreeableness were related to better clinician-assessed outcomes of group psychotherapy after 3 months 28 . While these results suggest that specific personality facets may be more useful than broader factors in predicting treatment outcomes, they do not yet present a clear pattern, and more research is needed to better articulate these relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That study, however, found no effects for depressiveness or warmth. Another small study, which did not measure depression severity, found that facets of openness and agreeableness were related to better clinician-assessed outcomes of group psychotherapy after 3 months 28 . While these results suggest that specific personality facets may be more useful than broader factors in predicting treatment outcomes, they do not yet present a clear pattern, and more research is needed to better articulate these relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Findings have been less consistent across studies for other FFM domains. Presence of depression was related to high N, low E, and low C 23 ; greater severity of symptoms was related to low E, low O, and low A 24 ; worse treatment outcomes were related to low O and low A 28 ; greater risk of developing new depression was related to low C 27 .…”
mentioning
confidence: 96%
“…13 Future investigations addressing the methodological issues raised above are needed to see whether the systematic assessment of personality factors may help to identify elderly depressed patients more prone to respond to a psychotherapeutic day hospital treatment and define adaptations of this care program to different personality styles. Supporting further the interest to assess personality profiles in elderly patients with depression, we recently demonstrated that Agreeableness and Openness to experience are also significant predictors of successful termination of group psychotherapy in this particular population.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 In respect to clinically overt psychopathology, NEO-PI domains have been associated with increased risk for suicidal ideation, 5 depression, anxiety, bipolar disorder, and schizophrenia. 13 In his early contribution, Miller 10 postulated that Neuroticism (N) influences the intensity of patient's distress, Extraversion (E) clients' enthusiasm for the therapy, Openness (O) patients' reaction to the therapist's interventions, Agreeableness (A) the subjective reaction of the client to therapist, and Conscientiousness (C) patients' possibility to invest psychotherapeutic work. 13 In his early contribution, Miller 10 postulated that Neuroticism (N) influences the intensity of patient's distress, Extraversion (E) clients' enthusiasm for the therapy, Openness (O) patients' reaction to the therapist's interventions, Agreeableness (A) the subjective reaction of the client to therapist, and Conscientiousness (C) patients' possibility to invest psychotherapeutic work.…”
mentioning
confidence: 99%
See 1 more Smart Citation